Characterization and Resilience of Upland Degraded Soils of Central Kalimantan - M ANANG FIRMANSYAH; . SUDARSONO; HIDAYAT PAWITAN; S DJUNIWATI; G DJAJAKIRANA (Balai Besar Penelitian dan Pengembangan Sumberdaya Lahan Pertanian, 2008)
In relation to land management and sustainable environment quality, soil degradation is considered as important issue. Soil degradation could be appropriately overcome when the characteristics of restoration or its resilience are recognized. The main purpose of this research is to characterize and classify upland degraded soils in Central Kalimantan based on land quality (LQ) that determine land suitability classification within landutilization type (LUT). The parameters of LQ involve water availability (w), nutrient availability (n), Al toxicity (t), soil resistance to erosion (e), and antropogenic soil deterioration (d). While, for LUT, there are several types i.e. rice; rice-rice-soybean; rubber; and oil palm within three patterns A, B, C. The other purpose is to characterize and classify degraded soils and soilresilience based on land index and land suitability classification. The parametric reffering to land index taken from production of commodity estimation within each LUT based on land quality is used to classify land suitability. Research result shows that Alfisols has the highest soil capability. It is indicated by land index that is higher than the other soils. The main indicators of soil degradation and resilience involve LQ of nutrient availability, water availability, and Al toxicity. The high soil potency does notshow the ability of resilience. On the other hand, the low soil potency cannot be able to keep sensitivity of degradation. The resistency of soils at study area is relatively high. Generally, degraded agricultural land region is difficult to be conserve through natural revegetation period known as bare land. Both natural and antropogenic resilience are not quite different atupland soils in Central Kalimantan. Soil taxa cannot reflect the difference of degrada